Design and Build Transport Manual Material Handling (MMH) Trolley Based on Ergonomic - Resy Kumala Sari; Yesi Yusmita (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to design and build a Transport Manual Material Handling (MMH) Trolley based on ergonomics by recruiting 100 students (45 female participants and 55 male participants) randomly from the Faculty of Engineering, Universitas Pahlawan Tuanku Tambusai. Anthropometric data measured in the form of Standing Elbow Height (TSB), Sitting Hand Reach (JTD), Hand Width to Metacarpal (LTM), Shoulder Width (LB), the data in the normality test can be seen that the chi-square count < chi table, the data above is normally distributed, the uniformity test states that from the 4 anthropometric data are uniform, and finally the adequacy test states that the data is normal (N'<N). The results of the test and the calculation of percentiles were obtained in the